Intergroup conflict, recategorization, and identity construction in Acts: breaking the cycle of slander, labeling and violence - Park, Hyun Ho (Library of New Testament studies, 2024)
"Hyun Ho Park analyzes Acts 21:17-23:35 in which the vicious cycle of slander, labeling, and violence is finally broken and the Lukan construction of Christian identity is challenged"--